Parametric and Non-Parametric Approaches to the Analysis of Adolscents' Knowledge and Attitudes on Tuberculosis - Findasari Findasari; Fitriana Kartikasari; Ivanna Isty Nursani; Ndaru Atmi Purnami (LPPM Universitas Terbuka, 2025)
Pulmonary tuberculosis (TB) remains a major public health problem in Indonesia. Improving adolescents’ knowledge and attitudes through school-based health education is essential to support TB prevention efforts. This study aimed to assess changes in knowledge and attitudes toward pulmonary tuberculosis following an audiovisual-based health education intervention. A quantitative pre-experimental one-group pretest–posttest design was conducted among 103 Grade XI students in a senior high school in Kudus Regency, Central Java. Data were collected using structured questionnaires. Normality was assessed prior to analysis; as most variables violated the normality assumption (p < 0.05), the Wilcoxon Signed-Rank Test was used as the primary statistical method, while the paired t-test was performed as a supplementary comparison analysis. The results showed a significant increase in knowledge scores from a median of 26 to 28 (Z = –4.865, p < 0.001, r = 0.48) and a significant improvement in attitude scores (Z = –7.383, p < 0.001, r = 0.73). The paired t-test produced consistent results, with a mean increase of 1.835 points in knowledge (95% CI: 1.177–2.493; Cohen’s d = 0.545) and 3.417 points in attitudes (95% CI: 2.717–4.118; Cohen’s d = 0.954). Normalized gain analysis indicated that improvement in knowledge was categorized as low, whereas improvement in attitudes reached the medium category. In conclusion, audiovisual-based health education was associated with positive changes in adolescents’ knowledge and attitudes regarding pulmonary tuberculosis. However, because the study was conducted in a single school using a pre-experimental design, the findings should be generalized with caution. Further controlled studies involving more diverse populations are recommended.